Silver-decorated and palladium-coated copper-electroplated fibers derived from electrospun polymer nanofibers - An, Seongpil; Kim, Yong Il; Jo, Hong Seok; Kim, Min-Woo; Lee, Min Wook; Yarin, Alexander L.; Yoon, Sam S. (ELSEVIER SCIENCE SA, 2017)
Here we introduce novel methods of forming silver (Ag) and palladium (Pd) fibers. The Ag and Pd fibers are fabricated by the combination of electrospinning, electroplating, and ion-exchange techniques. Their properties are characterized by scanning electron microscope with energy dispersive X-ray spectroscopy, sheet resistance meter, UV-Vis spectrophotometer, and X-ray photoelectron spectroscope. These non-woven metal fibers are free-standing and film-shaped with high electrical conductivity, as well as flexibility. Such properties are attractive for future applications of these materials in various electrochemical processes. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: CORE-SHELL NANOFIBERS; IMPACT COOLING ENHANCEMENT; NANO-TEXTURED SURFACES; PHOTOCATALYTIC ACTIVITY; PLATED NANOFIBERS; NOVEC 7300; COMPOSITES; NANOPARTICLES; RELEASE; FILMS